Makna Keterlibatan Frater Kongregasi SMM dalam Meningkatkan Pertumbuhan dan Perkembangan Imam Mahasiswa Katolik UNITRI Malang Melalui Katekese Marial - Yohanes Wilson B. Lena Meo; Kristoforus Juliano Ilham; Nur Oktavianus Yeval; Yulianus Lihong Nasar (Publisher STPKat, 2024)
Marial catechesis is a branch of contextual catechesis that is very popular today. The reason cannot be separated from the importance of the presence of Our Lady in the Church. Mother Mary has become an important figure recognized by the Church with various titles, even with her attitude and virtues she has been able to become an example for the lives of the faithful. Various groups pay homage to Our Lady, either through prayer, devotion, involvement in categorical groups, or participating in marial catechesis activities themselves. One of these groups is the Catholic students of Tribhuwana Tunggadewi University (UNITRI) Malang who have actively participated in marial catechesis activities facilitated by brothers from the Montfortan Marian Union (SMM) congregation. Therefore, this research aims to explore the meaning of the involvement of the brothers of the SMM congregation in enhancing the growth and development of the faith of UNITRI students through marial catechesis activities. Using qualitative descriptive methods, this research examines six meanings of the involvement of the brothers of the SMM congregation in increasing the growth and development of the faith of UNITRI Catholic students through marial catechesis activities.